Skala Prioritas Penggunaan Dana Desa di Kabupaten Semarang, Demak, dan Kendal - Ray Septianis Kartika; Sulasdiono Arief (Jurnal Kebijakan Pembangunan, 2021)
The priority scale in the use of village funds is an effort to take into account village needs during the planning process and when the budget is used. Its implementation must be relevant to community needs. Determining the priority scale will face problems if it gets intervention from the regional head. This study aims to identify the priority scale for village use by Government Regulation Number 60 of 2014 concerning Village Funds. This research is a descriptive qualitative type. The research focuses are Kendal, Demak, and Semarang Regency. Data were collected through interviews and Focus Group Discussions (FGD). The results of the study show that the determination of the priority scale is based on the needs and problems in each region. Semarang Regency is directed towards physical development; Demak Regency is directed at village governance, implementation of village development, community development, and empowerment of village communities; while the Kendal priority scale were village community development. This study recommends that there is a need for identification of program needs based on mapping of existing problems in the local area, it is necessary to carry out supervision to synchronize the APBDesa with the priority scale for the use of village funds as well as to follow up on the results of the monitoring report, and to include village cadres in the team that oversees the suitability of village fund proposals against priority scale and use of village funds.